What Slice of the Pie? : The Corporate Bond Market Boom in Emerging Economies - Ayala Pena, Diana (IMF Working Papers; Working Paper ;, 2015)
This paper studies the determinants of shifts in debt composition among EM non-financial corporates. We show that institutions and macro fundamentals create an enabling environment for bond market development. During the recent boom episode, however, global cyclical factors accounted for most of the variation of bond shares in total corporate debt. The sensitivity to global factors appears to vary with relative bond market size-which we interpret to be associated with liquidity and easy entry and exit-rather than local fundamentals. Foreign bank linkages help explain why bond markets increasingly substituted for banks in channeling liquidity to EMs. Our results highlight the risk of capital flow reversal in EMs that benefited from the upturn in the global financial cycle mostly due to their liquid markets rather than strong fundamentals.